2018
DOI: 10.1080/09712119.2018.1516670
|View full text |Cite
|
Sign up to set email alerts
|

Protease treatment of canola meal-containing Japanese quail diets: Effect on physiological parameters and meat quality traits

Abstract: The utility of canola meal as protein source for quails may be limited by trypsin inhibitors that interfere with protein digestion. This study was, therefore, designed to assess the effect of including a heatstable protease mono-enzyme (75'000 PROT/g; EC/IUB no. 3.4.21) in canola meal-containing diets on physiological and meat quality traits of adult female Japanese quails. A total of 240, five-week old quails (163.9 ± 9.56 g live-weight) were distributed into 30 replicate pens, to which five isocaloric and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
2
3
0
5
Order By: Relevance
“…Nonetheless, no dietary influences were observed for all the other blood parameters including the liver enzymes (ALKP and ALP), suggesting that partial replacement of soybean products with BSFL meal did not compromise the health status of the birds. Furthermore, the hemato-biochemical values reported in this study fell within the normal ranges reported for quails [3,26,27]. In addition, several studies also revealed no significant dietary effects on blood parameters of broilers [21], laying hens [22], and Barbary partridges [28] when fed with a variety of insect meals.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Nonetheless, no dietary influences were observed for all the other blood parameters including the liver enzymes (ALKP and ALP), suggesting that partial replacement of soybean products with BSFL meal did not compromise the health status of the birds. Furthermore, the hemato-biochemical values reported in this study fell within the normal ranges reported for quails [3,26,27]. In addition, several studies also revealed no significant dietary effects on blood parameters of broilers [21], laying hens [22], and Barbary partridges [28] when fed with a variety of insect meals.…”
Section: Discussionsupporting
confidence: 83%
“…This will inevitably lead to higher levels of atmospheric carbon [2] due to deforestation and land preparation activities. The demand for soybean, the main protein source in poultry diets, has also steadily increased due to competition between animal and human needs [3]. This has led to higher market prices for this vegetable protein thus compromising its contribution to food and nutrition security.…”
Section: Introductionmentioning
confidence: 99%
“…It was, therefore, expected that pre-treatment of the seaweed with both the protease mono-enzyme and cellulolytic multi-enzymes would improve the utilization of the diets resulting in improved digestibility and growth performance. The lack of improvement in the feed value of substrates treated with exogenous fibrolytic and protease enzymes has similarly been reported by Mnisi et al [26] and Mnisi and Mlambo [27] in Japanese quail fed canola-containing diets. Likewise, Sayyazadeh et al [28] reported no significant effects on body weight and feed efficiency of chickens fed cereal-based diets supplemented with exogenous enzymes.…”
Section: Growth Performance and Hemato-biochemical Parameterssupporting
confidence: 55%
“…It was recently reported that partial replacement of rapeseed meal did not harm chickens [200,201]. Moreover, Mnisi and Mlambo [202,203] investigated this replacement in Japanese quail diet and found that growth performance, health, and meat quality were not affected at a ratio of less or equal to 12.5%. However, feed intake decreased at 17.5% of rapeseed meal.…”
Section: Animal Foddermentioning
confidence: 99%